Composite negative electrode material and preparation method and application thereof
By preparing a composite anode material with a dense carbon clad layer on the negative electrode matrix material, the problems of low rate performance and poor low temperature performance in lithium-ion batteries and sodium-ion batteries are solved, and battery performance with higher capacity and faster charging and discharge are achieved.
Patent Information
- Application Number
- CN202311180492.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
AI Technical Summary
The existing negative electrode materials have problems such as low rate performance, poor low temperature performance, reduced capacity and poor fast charging performance in lithium-ion batteries and sodium-ion batteries.
By preparing a composite negative electrode material, it is coated with a dense carbon coating layer from the core of the negative electrode matrix material, and adjusting the microcrystalline carbon layer spacing of the carbon material by regulating the type of monomer and polymerization method, the stable and uniform coating of the polymer in the negative electrode matrix material is achieved.
The battery capacity and charge and discharge performance are improved, allowing the battery to achieve higher capacity and faster charge and discharge performance.
Smart Images

Figure BDA0004447143060000141
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and relates to a composite negative electrode material, a preparation method and uses thereof, and in particular to a composite negative electrode material that can be used in both sodium ion batteries and lithium ion batteries, a preparation method and uses thereof. Background Art
[0002] Recently, with the miniaturization and lightness of electronic instruments, the batteries used as their power sources also need to be miniaturized and lightened. As such miniaturized and lightened and high-capacity rechargeable / dischargeable batteries, lithium secondary batteries have been commercialized and used in portable electronic instruments such as small cameras, mobile phones and notebook computers, communication devices, etc.
[0003] Typically, a lithium secondary battery comprises a positive electrode (cathode), a negative electrode (anode) and an electrolyte. In addition, the lithium ions extracted from the positive electrode active material during the first charge are embedded in the negative electrode active material such as carbon particles, and are extracted again during discharge. In this way, because the lithium ions reciprocate between the positive and negative electrodes and transfer energy at the same time, charging / discharging can be achieved. Therefore, the negative electrode material is crucial to the impact on battery performance.
[0004] There are many types of negative electrode materials for secondary batteries. At present, graphite material is the most widely used raw material. However, due to the anisotropy of graphite crystals, there are problems such as low rate performance and poor low-temperature performance. In addition, during the battery charging and discharging process, the co-embedding of solvent molecules will destroy the structure of graphite, reducing its capacity and cycle time. Hard carbon has extremely strong fast charging performance and high specific capacity. It can be used as a negative electrode material alone or modified by mixing with graphite. However, hard carbon materials have a large specific surface area, resulting in low coulomb efficiency of negative electrode materials and low material density, which leads to a large amount of fine powder after crushing and low yield. Pure silicon negative electrode material has a specific capacity of up to 4200mAh / g, but its expansion rate during charging and discharging reaches, and it is very easy to pulverize and fail during the cycle.
[0005] Therefore, how to improve the performance of different types of negative electrode materials so that the battery can achieve higher capacity and faster charging and discharging performance is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a composite negative electrode material and a preparation method and use thereof. The preparation method provided by the present invention can achieve stable and uniform coating of the polymer on the negative electrode matrix material, and at the same time can adjust the microcrystalline carbon layer spacing of the carbon material in the shell, so as to be suitable for different types of negative electrode matrix materials, so that the battery can achieve higher capacity and faster charge and discharge performance.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a composite negative electrode material, the preparation method comprising the following steps:
[0009] Mixing monomers, initiators and solvents to conduct a preliminary reaction to obtain an oligomer precursor solution;
[0010] The oligomer precursor solution, the negative electrode matrix material and the cross-linking agent are mixed and cross-linked to obtain an intermediate, and the intermediate is carbonized to obtain the composite negative electrode material.
[0011] The oligomer in the present invention is an oligomer having a molecular weight of less than 10,000.
[0012] The preparation method provided by the present invention first obtains the oligomer, and then controls the main chain structure and molecular spatial configuration of the polymer by regulating the monomer type and polymerization method, thereby adjusting the appearance of the shell carbon material, the bulk structure and the spacing between the microcrystalline carbon layers; the in-situ cross-linking coating (liquid phase) method used by the present invention can achieve high-strength bonding between the carbon coating layer and the surface of the negative electrode particles, forming a dense polymer coating layer, and realizing stable and uniform coating of the polymer on the negative electrode matrix material. The cross-linked coating structure will not become viscous due to temperature increase during the carbonization process, and finally a dense and uniform coating layer is obtained, which can be applied to different types of negative electrode matrix materials, so that the battery can achieve higher capacity and faster charge and discharge performance.
[0013] In the present invention, if the monomer, initiator and cross-linking agent are directly mixed to carry out cross-linking polymerization coating of the negative electrode matrix material, the monomer will be randomly polymerized, that is, polymerized in the gaps between the negative electrode particles, making it partially physically mixed and unable to achieve uniform coating; and if the oligomer is used to coat the negative electrode matrix material, pure liquid phase coating without adding a cross-linking agent, the coating layer will be heated and viscous due to the carbonization process, resulting in an inability to obtain a uniform coating layer.
[0014] Preferably, the monomer further comprises O and / or N.
[0015] In the present invention, the monomer contains O and / or N. The O atoms affect the growth of the microcrystalline carbon layer during the carbonization process, increase the interplanar spacing, and then escape during the carbonization process to form closed micropores. This structure has more ion storage sites and good fast charging performance. The carbon layer obtained after carbonization is doped with N, and the lone pair electrons on the N atoms are conducive to the rapid conduction of ions.
[0016] Preferably, the monomer includes aromatic compounds and derivatives thereof containing polymerizable unsaturated carbon bond functional groups, preferably any one or a combination of at least two of alkenylbenzenes and their derivatives, alkenylnaphthalenes and their derivatives, alkenylphenanthrenes and their derivatives, furanbenzenes and their derivatives, indene and its derivatives, vinyl aromatic ether derivatives or bismaleimide derivatives.
[0017] The monomers provided by the present invention contain aromatic compounds and derivatives thereof containing polymerizable unsaturated carbon bond functional groups, which can realize chain polymerization of monomers and chemical crosslinking between molecular chains, while non-aromatic compounds are not conducive to chemical crosslinking between molecular chains.
[0018] Monomers include, but are not limited to, styrene, acrylbenzene, ethyl acrylbenzene, 2-allylphenol, 4-vinylphenol, 4-vinylanisole, 4-vinylphenylethyl ether or 2-vinylanisole, benzofuran, vinylnaphthalene, vinylphenanthrene, indene, N,N'-(4,4'-methylenediphenyl)bismaleimide, N,N'-(4,4'-diphenylether)bismaleimide, N,N'-m-phenylenebismaleimide, N,N'-p-phenylenebismaleimide or N,N'-(4-methyl-1,3-phenylene)bismaleimide, vinylpyrrolidone, vinylcaprolactam or N-vinylcarbazole, etc.
[0019] Preferably, the solvent comprises any one of tetrahydrofuran, toluene or quinoline, or a combination of at least two thereof.
[0020] Preferably, the initiator comprises a carbocation initiator, preferably any one or a combination of at least two of a protonic acid, a Lewis acid, a Lewis acid complex or other carbocation initiators, preferably a Lewis acid and / or a Lewis acid complex.
[0021] In the present invention, protonic acids include but are not limited to sulfuric acid, phosphoric acid, perchloric acid, trifluoroacetic acid, etc.; Lewis acid complexes include but are not limited to BF3, AlCl3, TiCl4, BF3-ether complex, etc.
[0022] Preferably, the other carbon cation initiator comprises any one of oxonium ions, perchlorates or cycloheptatriene salts, or a combination of at least two thereof.
[0023] In the present invention, when an oxonium ion initiator is used, a strong Lewis acid catalyst (AlCl3, FeCl3, TiCl4, aluminum chloride, zinc chloride, ferric chloride, titanium tetrachloride) needs to be additionally added during the mixed crosslinking process, and the added amount is 1 to 5% of the crosslinking agent content, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc.
[0024] Preferably, the amount of the initiator added is 1-5% of the monomer, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc.
[0025] Preferably, the preliminary reaction is carried out under a protective atmosphere.
[0026] Preferably, the temperature of the preliminary reaction is 60-80°C, such as 60°C, 65°C, 70°C, 75°C or 80°C.
[0027] Preferably, the initial reaction time is 1 to 4 hours, such as 1 hour, 2 hours, 3 hours or 4 hours.
[0028] Preferably, the molecular weight of the oligomer precursor is 300-2000, for example, 300, 500, 800, 1000, 1300, 1500, 1800 or 2000.
[0029] In the present invention, when the molecular weight of the oligomer precursor is between 300 and 2000, uniform coating of the resin layer can be achieved and high crosslinking can be achieved. If the molecular weight is too large, the steric hindrance of the reaction with the crosslinking agent will be too large due to the excessive length of the oligomer molecular chain, thereby affecting the crosslinking density. If the molecular weight is too small, the fluidity of the oligomer at room temperature will be too strong and coating cannot be achieved.
[0030] Preferably, the molar amount of the crosslinking agent is 10-50% of the molar amount of the monomer, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc.
[0031] In the present invention, if the cross-linking agent is excessive, it will escape during the carbonization process, resulting in a decrease in the vibration / compacted density of the material, while if the molar amount is too small, it will affect the cross-linking degree of the coating layer.
[0032] Preferably, the cross-linking agent includes any one of an aldehyde cross-linking agent, an olefin cross-linking agent, a halide cross-linking agent or an alcohol cross-linking agent, or a combination of at least two thereof.
[0033] Preferably, the aldehyde cross-linking agent includes any one of benzaldehyde, trioxymethylene, dimethylformal or polyformaldehyde, or a combination of at least two thereof.
[0034] In the present invention, the crosslinking agent is a substance having two or more functional groups or active sites that can undergo Friedel-Crafts reaction with the benzene ring structure, and the mixed crosslinking reaction includes the growth of the oligomer molecular chain and the crosslinking reaction between molecular chains (through the electrophilic substitution reaction of the crosslinking agent with the aromatic ring, such as aldehyde-aromatic ring, or Friedel-Crafts alkylation reaction).
[0035] Preferably, the vinyl crosslinking agent includes any one of divinylbenzene, ethylene glycol dimethacrylate, N,N-methylenebisolefinamide or triallyl cyanurate, or a combination of at least two thereof.
[0036] Preferably, the halogenated cross-linking agent includes any one of dichloromethane, chloroform, 1,2-dichloroethane or 1,3-dichloroethane, or a combination of at least two thereof.
[0037] Preferably, the temperature of the mixed cross-linking is 60-90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C.
[0038] Preferably, after the mixed cross-linking reaction is completed, Soxhlet extraction is performed.
[0039] Preferably, the solvent for the Soxhlet extraction includes any one of ethanol, propanol, tetrahydrofuran, acetone, cyclohexane, toluene, quinoline or N-methylpyrrolidone, or a combination of at least two thereof.
[0040] Preferably, the mixed cross-linked reactants are dried.
[0041] Preferably, the negative electrode matrix material includes any one of graphite, porous carbon, hard carbon or silicon-based negative electrode materials, or a combination of at least two thereof.
[0042] The composite negative electrode material obtained by the preparation method provided by the present invention has different base materials and different effects after being coated with a carbon layer.
[0043] The preparation method provided by the present invention can improve the gram capacity and fast charging performance of common graphite negative electrode materials.
[0044] When carbon is coated on hard carbon materials, the specific surface area is reduced and the vibration / compaction density and Coulomb efficiency are increased.
[0045] Furthermore, when carbon is coated on silicon-based materials, the specific surface area is effectively reduced, and the coulombic efficiency and electrical conductivity are improved.
[0046] Preferably, the mass ratio of the graphite to the monomer is (90-99):(10-1), for example, 90:10, 93:7, 95:5, 97:3 or 99:1.
[0047] Preferably, the mass ratio of the silicon-based negative electrode material to the monomer is (70-99):(30-1), for example, 70:30, 75:25, 80:20, 85:15, 90:10, 95:5 or 99:1.
[0048] Preferably, the mass ratio of the porous carbon to the monomer is (80-98):(20-2), for example, 80:20, 85:15, 90:10, 95:5 or 98:2.
[0049] Preferably, the mass ratio of the hard carbon to the monomer is (80-98):(20-2), for example, 80:20, 85:15, 90:10, 95:5 or 98:2.
[0050] Preferably, the carbonization includes performing a first carbonization and a second carbonization in sequence.
[0051] Preferably, the heating rates of the first carbonization and the second carbonization are each independently 1 to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 8°C / min or 10°C / min, etc., preferably 1 to 5°C / min.
[0052] Preferably, the temperature of the first carbonization is 250-400°C, for example, 250°C, 300°C, 350°C or 400°C.
[0053] Preferably, the first carbonization time is 1 to 4 hours, such as 1 hour, 2 hours, 3 hours or 4 hours.
[0054] Preferably, the temperature of the second carbonization is 800-1500°C, for example, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or 1500°C.
[0055] Preferably, the second carbonization time is 4 to 10 h, for example, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h.
[0056] As a preferred technical solution, the preparation method comprises the following steps:
[0057] Mixing monomers of aromatic compounds and derivatives thereof containing polymerizable unsaturated carbon bond functional groups, an initiator and a solvent, wherein the amount of the initiator added is 0.1-5% of the monomers, and performing a preliminary reaction at a reaction temperature of 60-80° C. for 1-4 hours under a protective atmosphere to obtain an oligomer precursor solution;
[0058] The oligomer precursor solution, the negative electrode matrix material and the crosslinking agent are mixed and crosslinked at 60-90° C., the molar amount of the crosslinking agent is 10-50% of the molar amount of the monomer, and then Soxhlet extraction is performed and dried to obtain an intermediate, and the intermediate is carbonized to obtain the composite negative electrode material.
[0059] In a second aspect, the present invention provides a composite negative electrode material, which is prepared by the preparation method as described in the first aspect, and the composite negative electrode material comprises a negative electrode matrix material inner core and a carbon coating layer located on the surface of the inner core.
[0060] In a third aspect, the present invention further provides a battery, comprising the composite negative electrode material as described in the second aspect.
[0061] Preferably, the battery comprises a lithium ion battery and / or a sodium ion battery.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] The preparation method provided by the present invention first obtains the oligomer, and then controls the main chain structure and molecular spatial configuration of the polymer by regulating the monomer type and the polymerization method, thereby adjusting the surface and bulk structure of the shell carbon material, and adjusting the spacing between the microcrystalline carbon layers of the carbon material in the shell obtained after carbonization, and then through the in-situ cross-linking coating (liquid phase) method, the carbon coating layer can be combined with the surface of the negative electrode particles with high strength, forming a dense polymer coating layer, realizing stable and uniform coating of the polymer on the negative electrode matrix material, the cross-linking structure will not be affected by heat and viscosity during the carbonization process, and finally a dense and uniform coating layer is obtained, which can be applicable to different types of negative electrode matrix materials, so that the battery can achieve higher capacity and faster charge and discharge performance. DETAILED DESCRIPTION
[0064] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0065] Example 1
[0066] This embodiment provides a composite negative electrode material, which includes an artificial graphite core and a carbon coating layer coated on the surface of the artificial graphite core.
[0067] The preparation method of the composite negative electrode material is as follows:
[0068] (1) 2-vinylanisole (monomer), N,N'-(4-methyl-1,3-phenylene)bismaleimide (the mass ratio of 2-vinylanisole to N,N'-(4-methyl-1,3-phenylene)bismaleimide is 7:3) and tetrahydrofuran are mixed and stirred at room temperature, and then perchloric acid (the amount of perchloric acid added is 2% of the monomer) is added under a nitrogen protective atmosphere, and the temperature is raised to 70° C. and the mixture is initially reacted for 2 hours to obtain a linear oligomer precursor (molecular weight 2000);
[0069] (2) In a kneading device, the artificial graphite material (the mass ratio of artificial graphite to monomer is 95:5) and the oligomer precursor solution are fully stirred to make the surface of the artificial graphite material fully infiltrated by the solution, and then the crosslinking agent trioxymethylene (the molar amount of trioxymethylene is 30% of the molar amount of 2-vinylanisole) is added, and the reaction is continued at 75° C., and the solvent is gradually evaporated so that the polymer completely crosslinks and coats the surface of the negative electrode material; using a Soxhlet extractor, unreacted monomers and oligomers are extracted with ethanol, and then the sample is dried at 100° C. and further crosslinked and cured to obtain an intermediate (crosslinked polymer-coated artificial graphite);
[0070] (3) The intermediate is placed in a carbonization device, an inert gas argon is introduced, the temperature is increased to 300°C at a heating rate of 5°C / min and kept at this temperature for 4 hours (first carbonization), and then the temperature is increased to 1000°C and kept at this temperature for 5 hours (second carbonization). After the temperature is naturally cooled, the material is taken out and processed through a 300-mesh vibrating screen to remove the material on the screen to obtain the composite negative electrode material.
[0071] Example 2
[0072] This embodiment provides a composite negative electrode material, which includes an artificial graphite core and a carbon coating layer coated on the surface of the artificial graphite core.
[0073] The preparation method of the composite negative electrode material is as follows:
[0074] (1) After mixing benzofuran (monomer) and quinoline at room temperature, anhydrous aluminum chloride (the amount of anhydrous aluminum chloride added is 5% of benzofuran) is added under a protective atmosphere of nitrogen, and the temperature is raised to 60° C. to allow a preliminary reaction for 2 hours to obtain a linear oligomer precursor (molecular weight of 300);
[0075] (2) In a kneading device, the artificial graphite material (the mass ratio of artificial graphite to vinyl aromatic ether derivative is 98:2) and the oligomer precursor solution are fully stirred to make the surface of the artificial graphite material fully infiltrated by the solution, and then a crosslinking agent, ethylene glycol dimethacrylate (the molar amount of ethylene glycol dimethacrylate is 10% of the molar amount of benzofuran) is added, and the reaction is continued at 90° C., and the solvent is gradually evaporated, so that the polymer completely cross-links and coats the surface of the negative electrode material; using a Soxhlet extractor, unreacted monomers and oligomers are extracted with ethanol, and then the sample is dried at 150° C. and further cross-linked and cured to obtain an intermediate (cross-linked polymer-coated artificial graphite);
[0076] (3) The intermediate is placed in a carbonization device, an inert gas argon is introduced, the temperature is increased to 400°C at a heating rate of 5°C / min and kept at this temperature for 4 hours (first carbonization), and then the temperature is increased to 1500°C and kept at this temperature for 4 hours (second carbonization). After the temperature is naturally cooled, the material is taken out and processed through a 500-mesh vibrating screen to remove the material on the screen to obtain the composite negative electrode material.
[0077] Example 3
[0078] This embodiment provides a composite negative electrode material, which includes an artificial graphite core and a carbon coating layer coated on the surface of the artificial graphite core.
[0079] The preparation method of the composite negative electrode material is as follows:
[0080] (1) Styrene, vinyl caprolactam (the mass ratio of styrene to vinyl caprolactam is 8:2) and tetrahydrofuran are mixed and stirred at room temperature, and then sulfuric acid (the amount of sulfuric acid added is 1% of the monomer) is added under a protective atmosphere of nitrogen, and the temperature is raised to 70° C. and the mixture is initially reacted for 4 hours to obtain a linear oligomer precursor (molecular weight of 1200);
[0081] (2) In a kneading device, the artificial graphite material (the mass ratio of artificial graphite to monomer is 97:3) and the oligomer precursor solution are fully stirred to make the surface of the artificial graphite material fully infiltrated by the solution, and then the crosslinking agent 1,2-dichloroethane (the molar amount of 1,2-dichloroethane is 50% of the molar amount of the monomer) is added, and the reaction is continued at 75° C., and the solvent is gradually evaporated so that the polymer completely crosslinks and covers the surface of the negative electrode material; using a Soxhlet extractor, unreacted monomers and oligomers are extracted with ethanol, and then the sample is dried at 100° C. and further crosslinked and cured to obtain an intermediate (crosslinked polymer-coated artificial graphite);
[0082] (3) The intermediate is placed in a carbonization device, an inert gas argon is introduced, the temperature is increased to 300°C at a heating rate of 5°C / min and kept at this temperature for 4 hours (first carbonization), and then the temperature is increased to 1000°C and kept at this temperature for 5 hours (second carbonization). After the temperature is naturally cooled, the material is taken out and processed through a 300-mesh vibrating screen to remove the material on the screen to obtain the composite negative electrode material.
[0083] Example 4
[0084] The difference between this embodiment and embodiment 1 is that the molecular weight of the oligomer in step (1) of this embodiment is 100.
[0085] The rest of the preparation methods and parameters were the same as those in Example 1.
[0086] Example 5
[0087] The difference between this embodiment and embodiment 1 is that the molecular weight of the oligomer in step (1) of this embodiment is 4000.
[0088] The rest of the preparation methods and parameters were the same as those in Example 1.
[0089] Example 6
[0090] The difference between this embodiment and embodiment 1 is that the molar amount of the cross-linking agent in step (2) of this embodiment is 5% of the molar amount of the monomer.
[0091] The rest of the preparation methods and parameters were the same as those in Example 1.
[0092] Example 7
[0093] The difference between this embodiment and embodiment 1 is that the molar amount of the cross-linking agent in step (2) of this embodiment is 55% of the molar amount of the monomer.
[0094] The rest of the preparation methods and parameters were the same as those in Example 1.
[0095] Example 8
[0096] The difference between this embodiment and embodiment 1 is that the cross-linking agent in step (2) of this embodiment is ethylenediamine.
[0097] The rest of the preparation methods and parameters were the same as those in Example 1.
[0098] Example 9
[0099] The difference between this embodiment and embodiment 1 is that the negative electrode matrix material in this embodiment is a hard carbon negative electrode material; and the mass ratio of the hard carbon negative electrode material to the monomer is 95:5.
[0100] The rest of the preparation methods and parameters were the same as those in Example 1.
[0101] Example 10
[0102] The difference between this embodiment and embodiment 1 is that the negative electrode matrix material in this embodiment is a silicon-oxygen negative electrode material; and the mass ratio of the silicon-oxygen negative electrode material to the monomer is 97:3.
[0103] The rest of the preparation methods and parameters were the same as those in Example 1.
[0104] Comparative Example 1
[0105] This comparative example provides a negative electrode material, which is the negative electrode base material in Example 1 (artificial graphite material, model KC1).
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 1 is that in this example, the artificial graphite material, monomer, perchloric acid, tetrahydrofuran and cross-linking agent trioxymethylene are directly mixed, and polymerized and cross-linked directly on the surface of the artificial graphite material.
[0108] The rest of the preparation methods and parameters were the same as those in Example 1.
[0109] Comparative Example 3
[0110] The difference between this comparative example and Example 1 is that the molecular weight of the polymer in step (1) of this comparative example is 100,000.
[0111] The rest of the preparation methods and parameters were the same as those in Example 1.
[0112] Comparative Example 4
[0113] The difference between this comparative example and Example 1 is that no cross-linking agent is added in step (2) of this comparative example.
[0114] The rest of the preparation methods and parameters were the same as those in Example 1.
[0115] Comparative Example 5
[0116] The difference between this comparative example and Example 9 is that in this example, the hard carbon negative electrode material, monomer, perchloric acid, tetrahydrofuran and cross-linking agent trioxymethylene are directly mixed and directly polymerized and cross-linked on the surface of the artificial graphite material.
[0117] The rest of the preparation methods and parameters were consistent with those in Example 9.
[0118] Comparative Example 6
[0119] The difference between this comparative example and Example 10 is that in this example, the hard carbon negative electrode material, monomer, perchloric acid, tetrahydrofuran and cross-linking agent trioxymethylene are directly mixed and directly polymerized and cross-linked on the surface of the silicon-oxygen material.
[0120] The rest of the preparation methods and parameters were the same as those in Example 10.
[0121] Lithium battery preparation:
[0122] A polyvinylidene fluoride solution with a mass fraction of 7% was prepared with N-methylpyrrolidone as solvent, and the negative electrode materials provided in Examples 1-10 and Comparative Examples 1-6 (excluding Example 9 and Comparative Example 5), polyvinylidene fluoride, and conductive carbon black were mixed evenly at a mass ratio of 80:10:10, and applied on copper foil. The coated electrode was placed in a vacuum drying oven at a temperature of 90°C and vacuum dried for 4 hours, and rolled to a surface density of 4-7 mg / cm 2 For standby use, a metal lithium sheet is used as the counter electrode, and a three-component mixed solvent of 1 mol / L LiPF6 with a mixture of EC:DMC:EMC=1:1:1 (volume ratio) is used as the electrolyte, and then assembled into a 2032-type button cell in an argon-filled glove box.
[0123] Sodium battery preparation:
[0124] The composite negative electrode material provided in Example 9 and Comparative Example 5 was mixed with the conductive agent SuperP, the mixture of sodium carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 94.5:1.5:1.5:2.5, and a proper amount of water was added to stir to form a slurry, and then the slurry was evenly coated on the current collector copper foil, and after drying, it was cut into a circular electrode with a diameter of 18 mm. Under vacuum conditions, the electrode was dried at 80°C for about 3 hours, vacuum dried at 80°C for 6 hours, and rolled to a surface density of 4-7 mg / cm 2The simulated battery was assembled in a glove box with an Ar atmosphere, using a sodium metal sheet as the counter electrode and 1M NaPF6 dissolved in ethylene carbonate solution as the electrolyte to form a CR2430 button cell.
[0125] Electrochemical performance testing of lithium batteries and sodium batteries:
[0126] The electrochemical performance test was performed on the batteries provided by Examples 1-8 and Example 10 and Comparative Examples 1-4 and Comparative Example 6, and the test conditions were that the charge and discharge voltage range was 5mV to 2.0V (lithium ion battery). The electrochemical performance test was performed on the batteries provided by Example 9 and Comparative Example 5, and the test conditions were that the charge and discharge voltage range was 0V to 2.0V (sodium ion battery). The first cycle effective capacity (mAh / g) and coulomb efficiency (%) (0.1C) were tested; the 3C lithium deposition SOC test was to discharge the button cell at a voltage range of 0V to 2.0V and a current of 3C, and characterize its starting lithium deposition point.
[0127] The results are shown in Table 1.
[0128] Table 1
[0129]
[0130] It can be seen from the data results of Example 1 and Examples 4 and 5 that if the molecular weight of the polymer is too large or too small, it will lead to degradation of the material capacity, initial efficiency and fast charging performance.
[0131] From the data results of Examples 1, 6 and 7, it can be seen that if the amount of cross-linking agent added is too little, it is not conducive to improving the fast charging performance of the material, while if the amount added is too much, the problem of initial effect degradation will occur.
[0132] It can be seen from the data results of Example 1 and Example 8 that the use of other types of cross-linking agents will not only lead to the degradation of the initial effect, but also fail to improve the fast charging performance of the material.
[0133] It can be seen from the data results of Example 1 and Comparative Example 1 that the composite negative electrode material obtained by the preparation method provided by the present invention has better fast charging performance than ordinary graphite negative electrode materials.
[0134] From the data results of Example 1 and Comparative Example 2, Example 9 and Comparative Example 5, and Example 10 and Comparative Example 6, it can be seen that the polymerization, cross-linking and coating are carried out simultaneously, which cannot effectively improve the fast charging performance of the material.
[0135] It can be seen from the data results of Example 1 and Comparative Example 3 that mixing, cross-linking and coating the polymer will result in the fast charging performance of the negative electrode material being unable to be effectively improved.
[0136] It can be seen from the data results of Example 1 and Comparative Example 4 that if a cross-linking agent is not added in step (2), a material with good fast charging performance cannot be obtained.
[0137] In summary, the preparation method provided by the present invention first obtains the oligomer, and then controls the main chain structure and molecular spatial configuration of the polymer by regulating the monomer type and polymerization method, thereby adjusting the surface and bulk structure of the shell carbon material, and adjusting the spacing between the microcrystalline carbon layers of the carbon material in the shell obtained after carbonization, and then through the in-situ cross-linking coating (liquid phase), a high-strength combination of the carbon coating layer and the surface of the negative electrode particles can be achieved, forming a dense polymer coating layer, achieving stable and uniform coating of the polymer on the negative electrode matrix material, and the cross-linking structure will not be affected by heat and viscosity during the carbonization process, and finally a dense and uniform coating layer is obtained, which can be applicable to different types of negative electrode matrix materials, so that the battery can achieve higher capacity and faster charge and discharge performance.
[0138] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite negative electrode material, characterized in that: The preparation method comprises the following steps: Mixing monomers, initiators and solvents to conduct a preliminary reaction to obtain an oligomer precursor solution; The oligomer precursor solution, the negative electrode matrix material and the cross-linking agent are mixed and cross-linked to obtain an intermediate, and the intermediate is carbonized to obtain the composite negative electrode material.
2. The method for preparing a composite negative electrode material according to claim 1, characterized in that: The monomer also includes O and / or N; Preferably, the monomer includes aromatic compounds containing polymerizable unsaturated carbon bond functional groups and their derivatives, preferably any one or a combination of at least two of alkenylbenzenes and their derivatives, alkenylnaphthalenes and their derivatives, alkenylphenanthrenes and their derivatives, furanbenzenes and their derivatives, indene and its derivatives, vinyl aromatic ether derivatives or bismaleimide derivatives; Preferably, the solvent comprises any one or a combination of at least two of tetrahydrofuran, toluene or quinoline; Preferably, the initiator comprises a carbocation initiator, preferably any one or a combination of at least two of a protonic acid, a Lewis acid, a Lewis acid complex or other carbocation initiators, preferably a Lewis acid and / or a Lewis acid complex; Preferably, the other carbocation initiator comprises any one or a combination of at least two of oxonium ions, perchlorates or cycloheptatriene salts; Preferably, the amount of the initiator added is 1-5% of the monomer.
3. The method for preparing a composite negative electrode material according to claim 1 or 2, characterized in that: The preliminary reaction is carried out under a protective atmosphere; Preferably, the temperature of the preliminary reaction is 60-80°C; Preferably, the initial reaction time is 1 to 4 hours; Preferably, the molecular weight of the oligomer precursor is 300-2000.
4. The method for preparing a composite negative electrode material according to any one of claims 1 to 3, characterized in that: The molar amount of the crosslinking agent is 10 to 50% of the molar amount of the monomer; Preferably, the cross-linking agent includes any one or a combination of at least two of an aldehyde cross-linking agent, an olefin cross-linking agent, a halide cross-linking agent or an alcohol cross-linking agent; Preferably, the aldehyde cross-linking agent includes any one of benzaldehyde, trioxymethylene, dimethylformal or polyformaldehyde, or a combination of at least two thereof; Preferably, the vinyl crosslinking agent includes any one or a combination of at least two of divinylbenzene, ethylene glycol dimethacrylate, N,N-methylenebisolefinamide or triallyl cyanurate; Preferably, the halogenated cross-linking agent includes any one of dichloromethane, chloroform, 1,2-dichloroethane or 1,3-dichloroethane, or a combination of at least two thereof.
5. The method for preparing a composite negative electrode material according to any one of claims 1 to 4, characterized in that: The temperature of the mixed cross-linking is 60 to 90°C; Preferably, after the mixed cross-linking reaction is completed, Soxhlet extraction is performed; Preferably, the solvent of the Soxhlet extraction comprises any one or a combination of at least two of ethanol, propanol, tetrahydrofuran, acetone, cyclohexane, toluene, quinoline or N-methylpyrrolidone; Preferably, the mixed cross-linked reactants are dried.
6. The method for preparing a composite negative electrode material according to any one of claims 1 to 5, characterized in that: The negative electrode matrix material includes any one or a combination of at least two of graphite, porous carbon, hard carbon or silicon-based negative electrode materials; Preferably, the mass ratio of graphite to monomer is (90-99):(10-1); Preferably, the mass ratio of the silicon-based negative electrode material to the monomer is (70-99):(30-1); Preferably, the mass ratio of the porous carbon to the monomer is (80-98):(20-2); Preferably, the mass ratio of the hard carbon to the monomer is (80-98):(20-2).
7. The method for preparing a composite negative electrode material according to any one of claims 1 to 6, characterized in that: The carbonization includes sequentially performing a first carbonization and a second carbonization; Preferably, the heating rates of the first carbonization and the second carbonization are each independently 1 to 10°C / min, preferably 1 to 5°C / min; Preferably, the temperature of the first carbonization is 250-400°C; Preferably, the first carbonization time is 1 to 4 hours; Preferably, the temperature of the second carbonization is 800-1500°C; Preferably, the second carbonization time is 4 to 10 hours.
8. The method for preparing a composite negative electrode material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Mixing monomers of aromatic compounds and derivatives thereof containing polymerizable unsaturated carbon bond functional groups, an initiator and a solvent, wherein the amount of the initiator added is 1 to 5% of the monomers, and performing a preliminary reaction at a reaction temperature of 60 to 80° C. for 1 to 4 hours under a protective atmosphere to obtain an oligomer precursor solution; The oligomer precursor solution, the negative electrode matrix material and the crosslinking agent are mixed and crosslinked at 60-90° C., the molar amount of the crosslinking agent is 10-50% of the molar amount of the monomer, and then Soxhlet extraction is performed and dried to obtain an intermediate, and the intermediate is carbonized to obtain the composite negative electrode material.
9. A composite negative electrode material, characterized in that: The negative electrode material is prepared by the preparation method according to any one of claims 1 to 8, and the composite negative electrode material comprises a negative electrode matrix material core and a carbon coating layer located on the surface of the core.
10. A battery, characterized in that: The battery comprises the composite negative electrode material as claimed in claim 9; Preferably, the battery comprises a lithium ion battery and / or a sodium ion battery.